ANALYSIS EFFECT OF EXCHANGE RATES AND INTEREST RATESOF BANK INDONESIA ON SHARE PRICE - Ciseta Yoda, Tilawatil (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2019)
Every company should be able to set the price of shares in accordance withmarket prices to make investors interested in investing shares in the capital market. This study aims to determine and analyze the effect of exchange rate and interest rate of Bank Indonesia Certificates on share price of Property and Real Estate company that was listed on the Indonesia Stock Exchange (IDX).This research is a quantitative descriptive, population in this study are allcompany property and real estate listing in IDX as many as 48 companies withsampling purposive sampling techniques in order to obtain a sample 30 property and real estate company on the Stock Exchange. Data analysis techniques in this study using classical assumption test and multiple linear regression test consisting of partial test (t test), simultaneous test (F test), and the determinant coefficient (R-Square). The results of this study indicate that partial and simultaneous exchange rate and interest rate variables SBI has significant influence on stock prices and real estate property company on the Stock Exchange Period 2014-2017. It can be concluded that there is a negative effect of exchange rates and stock prices with significant value of 0.048. There is a significant positive effect between the Bank Indonesia Certificaterates to stock price with the significantvalue of 0.000. Exchange and Interest Rates have significant effect on stock prices and real estate property company on the Stock Exchange.Keywords: Exchange rate, interest rate of Bank Indonesia Certificates, stock price.